Incidencias de las reformas tributarias 2017, en los estados financieros de las empresas de sector inmobiliario segmento construcción de vivienda en la ciudad de Guayaquil - Martillo Medina, Johanna Elizabeth (2019)
The development of the research of the present thesis is titled Incidences of the tax reforms 2017, in the financial statements of the companies of the real estate sector housing construction segment in the city of Guayaquil. To carry out our research, we worked in the northern sector of the city of Guayaquil, with the aim of obtaining the necessary information and to be able to determine that taxes in our country are an economic benefit for the development of our society, but it is also the Achilles talon of companies in Ecuador, tax regulations change every day but the economic policies that are used do not go according to tax changes. This generates great uncertainty in the construction sector since entrepreneurs do not have greater support from the authorities, in the research carried out in 2015 and 2016 for the real estate sector it was very disappointing since high production costs, safeguards , and the high interest rates, created a destabilization of the sector, many companies closed leaving unemployed people who are one of the main engines of the country………